Ideal Body Weight-Based Dosing of Rabbit Antithymocyte Globulin for Cost Minimization in Kidney Transplantation. (June 2021) - Bubik, Rachel J.; Peterson, Kristen T.; Myhre, Laura J.; Bernard, Stacy A.; Dean, Patrick; May, Heather P.
Introduction: Contemporary dosing strategies for rabbit anti-thymocyte globulin (rATG) in kidney transplantation aim to reduce cumulative exposure, minimizing long-term adverse events. The use of ideal body weight-based dosing has been trialed, however concern for increased rejection post-transplant exists due to lower doses of rATG. Research Questions: The primary aim of this study was to compare rejection rates between rATG dosing protocols using actual body weight and ideal body weight and secondarily to evaluate cost savings following protocol implementation. Design: This was a retrospective study surrounding implementation of an ideal body weight-based dosing protocol for rATG. We compared 75 kidney transplant recipients in whom rATG was dosed based on actual body weight (pre-protocol group) to 64 in whom dosing was based on ideal body weight (post-protocol group), following a nine-month washout. Results: The mean cumulative rATG dose in the pre-protocol group was 6.3 mg/kg of actual body weight. When ideal body weight was used in the post-protocol group, the mean dose was 4.5 mg/kg of actual body weight. The rejection rate was 18.7% pre-protocol and 23.4% postprotocol, which did not represent a statistically significant difference (p = 0.491). The actual annual cost savings after protocol implementation exceeded 162, 000, approximately 2, 500 per patient. Conclusion: Results suggest ideal body weight-based dosing of rATG may reduce exposure and cost, without significantly impacting the risk of rejection in kidney transplant recipients. More studies are needed to confirm these findings.